CRIMINALIZATION OF CIVIL SOCIETY AND INDONESIA ENVIRONMENTAL POLITICS: CASE STUDY OF TANJUNG BENOA RECLAMATION - Robertua, Verdinand (Sociae Polites, 2023)
There is a serious problem with Indonesia's environmental politics because the government supported policies that potentially harmed the environment, including the reclamation project. Reclamation has harmed the mangrove forest and coral reef, as well as the fishing area. Civil society questioned the commitment of Indonesia's government to protecting the mangrove forest in Indonesia. The problem is worsened when activists and indigenous communities are criminalized. Activists are threatened by legal action due to their political activism. This research attempted to understand the role of civil society in changing government decisions by using a case study of the cancellation of the reclamation plan in Tanjung Benoa, Bali. Primary data is obtained through direct observation in Tanjung Benoa, Bali, and supported by secondary data from journals, news outlets, and official reports. There are two main findings. Firstly, the criminalization of civil society showed that the contradiction of the Indonesian constitution and law enforcement is clearer. Secondly, the government finally canceled the reclamation project in Tanjung Benoa due to massive protests from communities and civil society. Keywords: Environmental Politics, Indonesia, Tanjung Benoa, Civil Society, Reclamation